Driving Green Innovation for Sustainable Performance: An Empirical Study of Micro Enterprises in North Sumatra, Indonesia - Sisca Sisca; Andy Wijaya; Christina Yanita Setyawati; Acai Sudirman (Journal of Management and Entrepreneurship Research, 2025)
Objective: This study aimed to investigate the key factors driving the adoption of green innovation and how the adoption relates to the enhancement of sustainable business performance in North Sumatra context. Research Design & Methods: A quantitative design was applied through structural equation modeling (SEM) with SmartPLS software, based on data previously collected from 371 Micro, Small, and Medium Enterprises (MSMEs) in food and beverage (F&B) sector. Findings: The results showed that organizational factors, human resources, and technology were significant drivers in implementing green innovation. The adoption of this innovation has been proven to contribute positively to the social and environmental aspects of sustainable performance, although it did not have a significant impact on the economic aspect. Implications & Recommendations: This study provided valuable insights on green innovation, a topic that has received limited scholarly focus in the context of North Sumatra MSMEs. It also offered more insights into previously unanswered questions regarding the determinants of green innovation adoption and their potential role in fostering sustainable performance among MSMEs. Contribution & Value Added: Theoretically, this study expanded the use of Resource-Based View (RBV) by emphasizing the importance of internal resource management directed toward environmentally sound innovation to achieve sustainable competitive advantage. Practically, the results provided strategic guidance for MSMEs and policymakers in designing resource-based policies to encourage transformation toward sustainability.